Sistem Informasi Penjualan Minyak Bulus Secara Online pada Produksi Rumah Tangga Berbasis Web: Online Bulus Oil Sales Information System for Web-Based Household Production - Putra, Riko Andrian; Hartati, Yuli (Jurnal Pendidikan Sains dan Komputer, 2025)
Almost every aspect of human life has been influenced by advances in information technology (IT) in recent decades. These advances have redefined the way we communicate, work, and interact with each other. Bulus oil is one of the traditional products that has long been known in Indonesian culture. It comes from the process of processing bulus fat, a type of freshwater turtle (genus Amyda), which is considered to have many benefits, especially for health. However, the process of promotion and management of information at Dayat Bulus Oil Household Production has not yet maximized the development of computer technology. To facilitate sales at Dayat Bulus Oil Household Production from ordering to transactions, as well as accurate and updated information that can be viewed without having to come directly to the Dayat Bulus Oil Store, the author provides a solution for building a web-based information system. In this study, the author uses the RAD method to develop the system and UML to model the system framework created. This method is designed to accelerate software development by reducing planning time and prioritizing rapid functional prototyping. The language used in this study is PHP. The results of this web-based information system research provide consumers with the ability to view various information directly from anywhere and anytime. Then, it makes it easier for the store to monitor all operations, such as checking orders, viewing sales reports, and providing the latest information to customers and visitors.